Τhe effect of silica nanoparticles on the thermomechanical properties and degradation behavior of polylactic acid. (November 2014) - Georgiopoulos, P; Kontou, E; Meristoudi, A; Pispas, S; Chatzinikolaidou, M
In this work a series of polylactic acid/SiO2 nanocomposites have been prepared by a melt mixing procedure. The dispersion quality was examined by scanning electron microscopy. To study the degradation behavior of the polylactic acid/nanocomposites prepared, the samples were immersed in a buffer solution at a temperature of 37℃ with a pH of 7.4 for a time period of up to 23 weeks. These conditions simulate those in the human body, appropriate in medical applications. In order to assess their suitability in biomedical applications, we investigated the biocompatibility of these materials in terms of cell viability, growth, and morphology. A good initial cell adhesion has been detected, supporting their potential use in bone tissue engineering applications. The hydrolytic degradation of polylactic acid, under the prescribed conditions, was studied by the molecular weight reduction in terms of size exclusion chromatography, whereas the progress of thermal stability of polylactic acid and polylactic acid/nanocomposites during aging was tested by thermogravimetric analysis. The evolution of the materials' thermomechanical properties during aging was studied by differential scanning calorimetry, dynamic mechanical analysis, and tensile testing. The crystallization behavior in polylactic acid and the way it is affected by the presence of nanofillers during degradation procedure has been studied and values of 44% crystallinity increment have been found. At the specific aging conditions studied, silica nanoparticles accelerate the degradability of polylactic acid, having a higher impact on Young's modulus, under the specified aging conditions, for 7 weeks and hereafter this acceleration is retarded, due to the crystallinity increment, as a result of the molecular weight reduction.